2013
DOI: 10.1128/iai.01345-12
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Regulation of OX40 Ligand in Immune Responses to Aspergillus fumigatus

Abstract: (1) and promoting the proliferation of distinct T helper (Th) cell subsets (2). CD11c ϩ is a transmembrane protein found on the surface of DCs. CD11c ϩ DCs are a critical DC subpopulation responsible for antigen-specific T cell activation (3). Human CD11c ϩ cells in peripheral blood express receptors for thymic stromal lymphopoietin (TSLP), an epithelial cell cytokine that can drive Th2 differentiation (4). Expression of TSLP is increased in antigeninduced allergen models (5), and Th2 responses downstream of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…In contrast, 1,25 OH-vitamin D3 substantially reduces OX40L expression while increasing expression of TGF-β in human blood CD11c + DCs and ameliorates allergic bronchopulmonary aspergillosis in cystic fibrosis patients (51). Murine study showed that the regulation of vitamin D3 on OX40L expression in DCs is mediated through alteration of NF-kB p50 binding in the OX40L promoter (52). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 1,25 OH-vitamin D3 substantially reduces OX40L expression while increasing expression of TGF-β in human blood CD11c + DCs and ameliorates allergic bronchopulmonary aspergillosis in cystic fibrosis patients (51). Murine study showed that the regulation of vitamin D3 on OX40L expression in DCs is mediated through alteration of NF-kB p50 binding in the OX40L promoter (52). …”
Section: Discussionmentioning
confidence: 99%
“…We therefore investigated whether OX40L is also involved in the Th2 responses induced by Aspergillus in human PBMCs. As TNF and IL-1 can modulate the expression of OX40L [28,29], we analysed whether blocking TNF or IL-1 would result in a different expression of OX40L in PBMCs. 5d).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is reported that TNF can increase OX40L expression in smooth muscle cells, significantly higher in asthmatic than non-asthmatic patients [28] and TNF can up-regulate OX40L promoter-activity [29], this mechanism appears to play a more prominent role in DC-driven Th2 responses [55].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This Th2 response is unable to clear the fungi, however, the resultant exuberant inflammation leads to the characteristic immunological and pathological changes associated with this condition . Recently, it has been shown that peripheral CD11c+, thymic stromal lymphopoietin‐activated dendritic cells from patients with ABPA and CF induce robust Th2 cytokine responses from CD4 + T‐cells; and, in vitro treatment with vitamin D blunted these responses . Moreover, vitamin D levels have been shown to be reduced in patients with ABPA complicating CF .…”
Section: Introductionmentioning
confidence: 99%